Metabolism Determination By Soft Computing Methods From Breath Molecules - Hatice Akman; Sedat Metlek; Ismail Bayraklı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The breath analysis is a non-invasive risk-free and painless method used to diagnose specific diseases. Since the breath analysis method is a new study field than the other methods, there are many unsettled standards and unknown parameters. Numerous complex metabolisms are constantly working in the human body. Therefore, there are numerous unknown molecular relationships. ANN can produce solutions in these unexplained situations.In our pilot study, breath of 19 healthy people has been analyzed. The TD / GC-MS method, which is an analytical method of breath analysis, has been used to detect molecules in the breaths. Using soft computing methods to the results of the 19 breath samples, the relation between fermentation and carbon hydrate metabolism has been associated with breath analysis technique. The results indicated that, there can be a relationship between these metabolisms. There must be done more studies for the exact results.